The treatment patterns, efficacy, and safety of nab®-paclitaxel for the treatment of metastatic breast cancer in the United States: results from health insurance claims analysis. Issue 1 (December 2015) - Liang, Caihua; Li, Ling; Fraser, Cindy; Ko, Amy; Corzo, Deyanira; Enger, Cheryl; Patt, Debra
Abstract Background nab -Paclitaxel is an albumin-bound formulation of paclitaxel approved for the treatment of metastatic breast cancer (MBC). This analysis was designed to characterize the treatment patterns, efficacy, and safety ofnab -paclitaxel for MBC treatment using health claims data from US health plans associated with Optum. Methods Women aged ≥ 18 years who initiatednab -paclitaxel for MBC treatment from January 1, 2005, to September 30, 2012, and who met eligibility criteria were selected from the Optum Research Database for this analysis. Patients were required to have complete medical coverage and pharmacy benefits, ≥ 6 months of continuous enrollment, and a diagnosis of MBC prior tonab -paclitaxel initiation. The pattern of use fornab -paclitaxel (eg, regimen, schedule, duration, and administration) and claims-captured toxicities were characterized by line of therapy. Overall survival (OS) and time to next therapy or death (TNTD) were described by line of therapy, regimen, and schedule. Results Of the 664nab -paclitaxel patients, 172 (25.9 %) received it as first-line therapy, 211 (31.8 %) as second-line therapy, and 281 (42.3 %) as third-line or later therapy. Overall, the majority of patients received monotherapy (61 %) and followed a weekly (71 %) rather than an every 3 weeks treatment schedule.nab -Paclitaxel was often (31.7 %) combined with targeted therapy (57.5 % with bevacizumab and 23.9 % with trastuzumab or lapatinib). The median duration of therapy was 128 days (4.2 months). For the overall population, median OS was 17.4 months (22.7, 17.4, and 15.1 months in first-, second-, and third-line or later therapy, respectively). Median TNTD was 6.1 months (7.1, 6.6, and 5.3 months in first-, second-, and third-line or later therapy, respectively). For patients aged ≤ 50 years or with ≥ 3 metastatic sites, median OS was 15.6 months. No new safety signal was identified. Conclusions In this US healthcare system, the majority of patients receivednab -paclitaxel as second-line or later therapy, monotherapy, and weekly treatment. The efficacy and safety outcomes ofnab -paclitaxel observed in this real-world setting appear consistent with those from clinical trial data.